Separation of Three Monosaccharides Using Amino Ionic Liquid-Based Silica - Tian, Minglei; Tang, Baokun; Ho Row, Kyung (Asian Journal of Chemistry, 2015)
An amino-imidazolium ionic liquid was coated on commercial silica and the resulting ionic liquid-based particles were used as special sorbents of solid-phase. The mobile phase of acetonitrile/water from 90:10 to 70:30 (v/v) could separate the monosaccharides. Good linearity was obtained from 1 to 10 mg/mL with a RSD < 3.4 %. The sorbent produced reproducible results and performed stably, highlighting its potential as a separation material.